EU and EEU: Problems and Prospects of the Cooperation in the Current Geopolitical Conditions - Maria Lvovna Lagutina (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
This article is devoted to analysis of the current state and prospects of development of the relationships of two integration structures: the Eurasian economic Union (EEU) and the European Union (EU). The article focuses on the evolution of the concept of the Greater Europe; the author analyzes the main stages of development of the bilateral relations of the EU with the countries-members of the EEU. The author notes that in spite of the fact that in the current geopolitical conditions a dialogue between the EU and the EEU is difficult , there is an objective necessity to establish close relations between two blocks due to historical and geographical and the current geopolitical and geo-economic factors. However, nowadays the possibility of the convergence of these two integration projects can be realized within the traditional paradigm of «the Greater Europe from Lisbon to Vladivostok», but as a part of the «the Greater Eurasia from Lisbon to Shanghai».